Tatalaksana dan Pencegahan Pielonefritis Akut (Literature Review) - Ufairah Ariqah Heru; Agustina, Agustina (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Acute pyelonephritis is a bacterial infection in the kidneys and should be suspected in patients with pelvic pain and laboratory evidence of urinary tract infection. (Herness et al., 2020). Incidence of acute pyelonephritis is rising worldwide (Nurislami et al., 2023), United States, occurrences of acutely occurring pyelonefritis as many as 250,000 visits (Herness et al., 2020). Acute pyelonephritis is defined as the presence of the following two conditions: (a) axial temperature of 38.3°C or shivering; (b) pelvic pain or pain with costovertebral angular pressure; and (c) mixional syndrome. (Umesha et al., 2018). Supportive examination is an evaluation of the upper bladder with an ultrasound. (Penta et al., 2020). Treatment can be done in hospital or on the street. Implementation of proper ambulatory care is performed in patients with pyelonephritis without complications who are able to tolerate oral antibiotics and have no clinical signs of sepsis (Herness et al., 2020). Patient education and improved self-management have been identified as an important element of treatment (Hudson & Mortimore, 2020). Seven articles were selected based on inclusion criteria, publication date from 2020 until now regarding acute pyelonephritis.